2015
DOI: 10.18632/oncotarget.3696
|View full text |Cite
|
Sign up to set email alerts
|

miR-942 promotes cancer stem cell-like traits in esophageal squamous cell carcinoma through activation of Wnt/β-catenin signalling pathway

Abstract: The Wnt/β-catenin signalling pathway is known to play a vital role in the maintenance of cancer stem cells (CSCs), which are reported to be the origine of malignant cancers, and result in poor prognosis of multiple kinds of cancer. Therefore, it is of great importance to illuminate the mechanism by which the Wnt/β-catenin pathway regulates the cancer stem cell-like traits in cancers. Here, we report that miR-942 is significantly upregulated in esophageal squamous cell carcinoma (ESCC), and miR-942 levels are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
59
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 46 publications
3
59
0
Order By: Relevance
“…Similarly, miR-429 contributes to hepatocyte self-renewal, malignant proliferation, tumorigenicity, and chemoresistance, making it an attractive potential target to inactivate tumor-initiating cells in the liver (33). We show that miR-644a functions as an upstream activator of the Wnt/b-catenin pathway in ESCC, a pathway well characterized in the development of stem cell-like properties in a wide variety of cancer types, including ESCC (25,26). Therefore, we hypothesized that the levels of miR-644a could influence the stemness of ESCC cells via regulation of PITX2.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, miR-429 contributes to hepatocyte self-renewal, malignant proliferation, tumorigenicity, and chemoresistance, making it an attractive potential target to inactivate tumor-initiating cells in the liver (33). We show that miR-644a functions as an upstream activator of the Wnt/b-catenin pathway in ESCC, a pathway well characterized in the development of stem cell-like properties in a wide variety of cancer types, including ESCC (25,26). Therefore, we hypothesized that the levels of miR-644a could influence the stemness of ESCC cells via regulation of PITX2.…”
Section: Discussionmentioning
confidence: 82%
“…Various studies have documented that the Wnt/b-catenin signaling pathway is constitutively activated in many types of human cancer, and plays an important role in triggering aggressive cellular features that constitute a malignant phenotype (23)(24)(25). It was reported that PITX2 and the Wnt/b-catenin pathway exert positive-feedback regulation, while aberrant activation of Wnt/b-catenin signaling is strongly involved in ESCC tumorigenesis and/or progression (8,26). These results collectively suggest that the Wnt/b-catenin axis is one of the critical downstream pathways activated by PITX2 accumulation in ESCC malignancy that we now propose is miR-644a-mediated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-942 is inversely correlated with the expression of interferon-stimulated gene 12a (ISG12a) and modulates tumor necrosis factor-related apoptosisinducing ligand (TRAIL) sensitivity in cancer tissues and cells (77). Recently, miR-942 was shown to be upregulated in esophageal squamous cell carcinoma (ESCC) and to promote the stem cell-like traits by inhibiting three negative regulators of the Wnt/ ␤-catenin pathway, including secreted Frizzled-related protein 4 (sFRP4), glycogen synthase kinase 3␤ (GSK3␤), and transducinlike enhancer of split 1 (TLE1) (78). In addition, the high expression levels of miR-942 have been detected in nephrotic syndrome patients and lung cancer cases (79,80).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of PI3K-AKT-mTOR is frequent in melanoma and indicates a poor prognosis, and thus inhibition of the mTOR pathway will benefit numerous patients in the clinic (29). Ge et al (30) demonstrated that through abnormal activation of Wnt/β-catenin pathway, miR-942 aided to maintain cancer stem cell-like traits in ESCC, inducing poor prognosis and unsatisfactory drug effects. In addition, GSK-3β can promote esophagus carcinoma cells metastasis and spread by degrading β-catenin (31,32).…”
Section: Discussionmentioning
confidence: 99%